A chemosynthetic weed: the tubeworm Sclerolinum contortum is a bipolar, cosmopolitan species. (December 2015) - Georgieva, Magdalena; Wiklund, Helena; Bell, James; Eilertsen, Mari; Mills, Rachel; Little, Crispin; Glover, Adrian
Abstract Background Sclerolinum (Annelida: Siboglinidae) is a genus of small, wiry deep-sea tubeworms that depend on an endosymbiosis with chemosynthetic bacteria for their nutrition, notable for their ability to colonise a multitude of reducing environments. Since the early 2000s, aSclerolinum population has been known to inhabit sediment-hosted hydrothermal vents within the Bransfield Strait, Southern Ocean, and whilst remaining undescribed, it has been suggested to play an important ecological role in this ecosystem. Here, we show that the Southern OceanSclerolinum population is not a new species, but more remarkably in fact belongs to the speciesS. contortum, first described from an Arctic mud volcano located nearly 16, 000 km away. Results Our new data coupled with existing genetic studies extend the range of this species across both polar oceans and the Gulf of Mexico. Our analyses show that the populations of this species are structured on a regional scale, with greater genetic differentiation occurring between rather than within populations. Further details of the external morphology and tube structure ofS. contortum are revealed through confocal and SEM imaging, and the ecology of this worm is discussed. Conclusions These results shed further insight into the plasticity and adaptability of this siboglinid group to a range of reducing conditions, and into the levels of gene flow that occur between populations of the same species over a global extent.